STUDI PERBANDINGAN MUTU PELAYANAN KESEHATAN DENGAN KEPUASAN PASIEN BPJS DAN NON BPJS DI PUSKESMAS BEJI TAHUN 2023 - Anggia Murti Adam, (2023)
Quality and equitable health services are a basic need for everyone. Good service can be judged by its quality as seen from patient satisfaction. Public health center must be able to provide fair health services without differentiating the types of health financing for patients. The purpose of this study was to obtain a comparison of the quality of health services to the level of satisfaction of BPJS and Non BPJS patients at the Puskesmas Beji with the dimensions used being effective, safety, people-centered, timely, efficient, and equitable. This study used a quantitative method with a cross-sectional approach with a sample of 176 BPJS and Non-BPJS patient respondents. Data collection was carried out in April-May 2023 using a questionnaire and data analysis using the Mann-Whitney U test. The results showed that there were differences in patient satisfaction with BPJS and Non-BPJS based on the dimensions of effectiveness, patient-oriented, timely, efficient and equitable with ρ sig (2-tailed) = 0.000 and safety with ρ sig (2-tailed) = 0.004. This research is an evaluation material for the Puskesmas Beji to improve health services that refer to the quality dimension so as to increase patient satisfaction according to procedures. Keyword: Patient Satisfaction, Quality of Health Service, BPJS and Non-BPJS Patients.